OFF RECORDS STRATEGIES USED IN BILLBOARD CAMPAIGN: AN ANALYSIS OF LINGUISTICS PHENOMENA - Puspita Sari, Rosdiana; Hadiati, Chusni; Muttaqin, Usep (Jurnal Ilmiah Bina Bahasa, 2025)
In 2024, Indonesia held a general election. It included the presidential and legislative candidate elections. The peaceful and successful implementation of the campaign can support the realization of the Sustainable Development Goals, namely by achieving good health and well-being as well as decent work and good economic growth. The candidates used billboards as campaign media to reach society. The billboards contain picture, slogan or promises in order to get the voters. Some of the legislative candidates used implicit message in delivering their statements. This research aims to analyse the off-record strategies on billboards of prospective presidential and legislative members. The research uses qualitative method which explain linguistic phenomena by examining linguistic and non-linguistic context in the data. The result shows that there are five off record strategies which are found. They are giving hints to make message clear, giving association clue to make subtle suggestion, be incomplete to make assumed understanding, overstate for  exaggerating importance and metaphor to make analogical comparison. Giving association and metaphor are the two data which appear most.